Effect of 5α-Reductase Inhibitors on Sexual Function: A Meta-Analysis and Systematic Review of Randomized Controlled Trials. Issue 9 (1st September 2016) - Liu, Luhao; Zhao, Shankun; Li, Futian; Li, Ermao; Kang, Ran; Luo, Lianmin; Luo, Jintai; Wan, Shawpong; Zhao, Zhigang
ABSTRACT: Introduction: 5α-Reductase inhibitors (5ARIs) are widely used for the treatment of benign prostatic hyperplasia (BPH) and androgenetic alopecia (AGA). Aim: To review all the available data on the effect of 5ARIs on sexual function and assess whether 5ARIs increase the risk of sexual dysfunction. Methods: A systematic search of the literature was conducted using the Medline, Embase, and Cochrane databases. The search was limited to articles published in English and up to October 2015. Article selection proceeded according to the search strategy based on Preferred Reporting Items for Systematic Reviews and Meta-analyses criteria. Data were analyzed using Stata 12.0. A fixed- or a random-effects model was used to calculate the overall combined risk estimates. Publication bias was assessed using Begg and Egger tests. Main Outcome Measures: Sexual dysfunction, erectile dysfunction, and decreased libido. Results: After screening 493 articles, 17 randomized controlled trials with 17, 494 patients were included. Nine studies evaluated the efficacy of 5ARIs in men with BPH. The other eight reported using 5ARIs in the treatment of men with AGA. The mean age of participants was 60.10 years across all studies. We included 10 trials (6, 779 patients) on the efficacy and safety of finasteride, 4 trials (6, 222 patients) on the safety and tolerability of dutasteride, and 3 trials (4, 493 patients) using finasteride and dutasteride for AGA. The pooled relative risks for sexual dysfunction were 2.56 (95% CI = 1.48–4.42) in men with BPH and 1.21 (95% CI = 0.85–1.72) in men with AGA; those for erectile dysfunction were 1.55 (95% CI = 1.14–2.12) in men with BPH and 0.66 (95% CI = 0.20–2.25) in men with AGA; and those for decreased libido were 1.69 (95% CI = 1.03–2.79) in men with BPH and 1.16 (95% CI = 0.50–2.72) in men with AGA. Estimates of the total effects were generally consistent with the sensitivity analysis. No evidence of publication bias was observed. Conclusion: Evidence from the randomized controlled trials suggested that 5ARIs were associated with increased adverse effects on sexual function in men with BPH compared with placebo. However, the association was not statistically significant in men with AGA. Well-designed randomized controlled trials are indicated to study further the mechanism and effects of 5ARIs on sexual function.